Peritoneal Dialysis Aggravates and Accelerates Atherosclerosis in Uremic ApoE−/− Mice - Jamie Kane; Winnie G. Vos; Laura A. Bosmans; Bram W. van Os; Myrthe den Toom; Sanne Hoeksema‐Hackmann; Denise Moen‐de Wit; Marion J. Gijbels; Linda Beckers; Aldo Grefhorst; Johannes H. M. Levels; Lily Jakulj; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atherosclerosis is highly prevalent in people with chronic kidney disease (CKD), including those receiving peritoneal dialysis (PD). Although it is lifesaving, PD induces profound systemic inflammation, which may aggravate atherosclerosis. Therefore, the hypothesis is that this PD‐induced inflammation aggravates atherosclerosis via immune cell activation. Methods and Results ApoE−/− mice were subjected to a 5/6 nephrectomy to induce CKD. Three weeks later, mice were fed a high‐cholesterol diet. Half of the nephrectomized mice then received daily peritoneal infusions of 3.86% Physioneal for 67 further days (CKD+PD) until the end of the experiment, and were compared with mice without CKD. Sham operated and PD‐only mice were additional controls. CKD+PD mice displayed more severe atherosclerotic disease than control mice. Plaque area increased, and plaques were more advanced with a vulnerable phenotype typified by decreased collagen content and decreased fibrous cap thickness. Increased CD3+ T‐cell numbers were present in plaques and perivascular adipose tissue of CKD and CKD+PD mice. Plaques of CKD+PD mice contained more iNOS+ immune cells. Spleens of CKD+PD mice showed more CD4+ central memory, terminally differentiated type 1 T‐helper (Th1), Th17, and CX3C motif chemokine receptor 1+ (CX3CR1) CD4+ T‐cells with less regulatory and effector T‐cells. Conclusions PD‐fluid exposure in uremic mice potentiates systemic and vascular T‐cell‐driven inflammation and aggravates atherosclerosis. PD polarized CD4+ T‐cells toward an inflammatory Th1/Th17 phenotype, and increased CX3CR1+ CD4+ T‐cells, which are associated with vascular homing in CKD‐associated atherosclerosis. Targeting CD4+ T‐cell activation and CX3CR1+ polarization has the potential to attenuate atherosclerosis in PD patients.